The Benefits of the Management Information System for Small and Medium Enterprises (SMEs) on the Quality Management System - Tirtana Brachnata, Nur Wening (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increasing number of Small and Medium Enterprises (SEMs) is one of the important factors in the economic growth of a country. In improving the performance of SEMs, management information systems are thought to be able to play a positive role in the progress of SEMs. However, there are not many studies that summarize the extent to which management information systems are able to provide benefits to the SEMs sector. This paper is a literature review that discusses management information systems in decision making, especially in the field of SEMs. The review is carried out on articles with the topic of management information systems or decision-making systems, especially those related to the SEMs sector. We identified about 22 articles published in the last decade then analyzed and drew conclusions. The purpose of this study is to see the benefits provided by management information systems, especially in the SEMs sector. In this study it is known thatthe use of management information systems in SEMs has been reported by various studies. It is known that management information systems provide many benefits to SEMs such as helping in the field of production, capturing, storing, data integration, decision making, reporting, resource management, strategy formulation.